2020
DOI: 10.1111/jdi.13325
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo‐hyperglucagonemia was observed in pancreatectomized patients when measured by glucagon sandwich enzyme‐linked immunosorbent assay

Abstract: Glucagon is detected in plasma even after total pancreatectomy, and it is debated whether this glucagon is derived from the gastrointestinal tract. Here, we applied sandwich enzyme‐linked immunosorbent assay (ELISA) and liquid chromatography–high‐resolution mass spectrometry to measure plasma glucagon levels in one patient after partial pancreatectomy (one‐seventh of the pancreas remaining) and three patients after total pancreatectomy. Sandwich ELISA detected higher glucagon levels in pancreatectomy patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“… 28 , 29 However, when GLP-1 secretion is high, some glucagon assays cross-react with longer proglucagon-derived species containing the glucagon sequence, particularly glicentin, leading to debate over whether the gut ever releases intact glucagon. 30 , 31 In addition to these reports from populations with altered pathology, and although we were unable to find active glucagon in human intestinal tissue by LC-MS, 32 our data suggest that some healthy people may also exhibit post-OGTT glucagon elevation.…”
Section: Discussionsupporting
confidence: 47%
“… 28 , 29 However, when GLP-1 secretion is high, some glucagon assays cross-react with longer proglucagon-derived species containing the glucagon sequence, particularly glicentin, leading to debate over whether the gut ever releases intact glucagon. 30 , 31 In addition to these reports from populations with altered pathology, and although we were unable to find active glucagon in human intestinal tissue by LC-MS, 32 our data suggest that some healthy people may also exhibit post-OGTT glucagon elevation.…”
Section: Discussionsupporting
confidence: 47%
“…15,16 Thus, it has been reported that in the case of elevated proglucagon-derived peptide levels, such as after bariatric surgery or pancreatectomy, the currently used ELISA shows falsely high glucagon values due to cross-reactivity with these peptides. [16][17][18] In order to solve this problem, a modified protocol of the currently used ELISA has been reported. 16,17 As an alternative, we have developed a new sandwich ELISA using newly developed monoclonal antibodies against glucagon.…”
Section: Introductionmentioning
confidence: 99%
“…However, the currently used ELISA still has cross‐reactivities with proglucagon‐derived peptides due to their remaining non‐specific reaction with the antibodies used in this system 15,16 . Thus, it has been reported that in the case of elevated proglucagon‐derived peptide levels, such as after bariatric surgery or pancreatectomy, the currently used ELISA shows falsely high glucagon values due to cross‐reactivity with these peptides 16–18 . In order to solve this problem, a modified protocol of the currently used ELISA has been reported 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…It is reported that postprandial pseudohyperglucagonemia could be displayed when the plasma glucagon level was measured by glucagon sandwich ELISA after partial but large pancreatectomy (oneseventh of the pancreas remaining) and total pancreatectomy, possibly due to the cross-reactivity of glucagon antibodies to the remaining gut-derived glicentin [35]. In the current study, we could not exactly evaluate the dissected and remaining volumes of pancreatic parenchyma.…”
Section: Discussionmentioning
confidence: 63%